2020
DOI: 10.12717/dr.2020.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl) Phthalate (DEHP) and Uterine Histological Characteristics

Abstract: Phthalates have a long industrial history. It is suspected that phthalates and their metabolites have detrimental effects on reproduction and development. They are well-known for their anti-androgenic effects. Several studies have indicated that phthalates and their metabolites are reprotoxic in males and endocrine disruptors. Reproduction and embryogenesis occur in the uterus of female eutherian mammals. A horizontal analytical method is preferred to elucidate the toxic effects of phthalates on human reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 125 publications
2
13
0
Order By: Relevance
“…As the previous results, the possibility of chronic exposures to low-dose DEHP is an effect as EDC in the uterus without effect on F1 fertility (Cha et al, 2017;Cheon, 2020). Chronic low dose exposure of DEHP caused increase the uterine wet weight, endometrial thickness, and the number of glands (Cheon, 2020). Besides, it caused decreased expression of estrogen receptors in uterus.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…As the previous results, the possibility of chronic exposures to low-dose DEHP is an effect as EDC in the uterus without effect on F1 fertility (Cha et al, 2017;Cheon, 2020). Chronic low dose exposure of DEHP caused increase the uterine wet weight, endometrial thickness, and the number of glands (Cheon, 2020). Besides, it caused decreased expression of estrogen receptors in uterus.…”
Section: Introductionsupporting
confidence: 73%
“…Recently, there are many scientists suggest that low dose phthalate impacts on health of animals such as fertility and steroidogenesis (Bloom et al, 2015) and become a big issue in this field (Vandenberg et al, 2019). As the previous results, the possibility of chronic exposures to low-dose DEHP is an effect as EDC in the uterus without effect on F1 fertility (Cha et al, 2017;Cheon, 2020). Chronic low dose exposure of DEHP caused increase the uterine wet weight, endometrial thickness, and the number of glands (Cheon, 2020).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Several evidences suggested that environmental pollutants might be involved in the pathogenesis of endometriosis 7‐11 . These endocrine‐disrupting chemicals interrupt hormonal homeostasis and result in estrogen signaling changes 11‐23 …”
Section: Introductionmentioning
confidence: 99%